Znaczenie kontekstu w misji Ad gentes - Górski, Jan (Śląskie Studia Historyczno-Teologiczne, 1996)
This article belongs to new mission theology. It is an attainments in Polish bibliography and makes possible to know method and problems of missions in contextualization theology. The inculturation is as well an art as a method of mission in the all world. As a method it contains different mission fields. At first of all it contains liturgy, sacral music, art and canon law. But the inculturation contains all theology also. Above problems are dealt in this work. The result of the study is problem of contextualization. In the light of contextualization theology it is necessary to put question about the meaning of mission. The aim of this work is to answer the question, which is theology of mission in post - council theology. Sources of studies are documentation of the regional bishops’ conferences: of Asia (FABC), of Africa (SECAM) and Latin America (CELAM) and new missiological literature from non-european countries. On the base of contextualization dimension of mission theology we can build three models - in Asiatic context - means the problem of non-christian religions. The second models is the meeting with different cultures. This is African context. The third - Latin American model - means the help in development and as result of theology of liberation. Above three missiological models, three examples of contextualization are very important in the preparation of mission work. The theoretical work, peculiarity farther development of missiology, is built on the base of missiology and ecclesiology. Now the next question appears: which is role of particular churches. In the mission activity a center point lies on particular - continental churches. Rome as a center of mission has the task to co-ordinate this work. For missiology as a part of theology, new dimension appears: to take into consideration the contextualization problem. In the crisis of missiology this study is a proposition which contains idea of II Vatican Council and it may be a new point of start to farther theoretical studies and impulse for mission practice